2013
DOI: 10.1186/1742-9994-10-62
|View full text |Cite
|
Sign up to set email alerts
|

Effects of social disruption in elephants persist decades after culling

Abstract: BackgroundMulti-level fission-fusion societies, characteristic of a number of large brained mammal species including some primates, cetaceans and elephants, are among the most complex and cognitively demanding animal social systems. Many free-ranging populations of these highly social mammals already face severe human disturbance, which is set to accelerate with projected anthropogenic environmental change. Despite this, our understanding of how such disruption affects core aspects of social functioning is sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 46 publications
0
61
0
Order By: Relevance
“…the matriarchs) will make the other elephants in the group leave the area, and they put pressure on the government to translocate these individuals. However, this action will actually leave the other elephants confused and likely to act more aggressively (McComb et al, 2001;Shannon et al, 2013). Limited research has been carried out and published on the post-release movements of translocated elephants in Malaysia (Peninsular Malaysia: St€ uwe et al, 1998).…”
Section: Lack Of General Awarenessmentioning
confidence: 99%
“…the matriarchs) will make the other elephants in the group leave the area, and they put pressure on the government to translocate these individuals. However, this action will actually leave the other elephants confused and likely to act more aggressively (McComb et al, 2001;Shannon et al, 2013). Limited research has been carried out and published on the post-release movements of translocated elephants in Malaysia (Peninsular Malaysia: St€ uwe et al, 1998).…”
Section: Lack Of General Awarenessmentioning
confidence: 99%
“…The eldest matriarchs are also more likely to seek out additional cues—for example, by engaging in exploratory smelling—when calls were recognized as unfamiliar, perhaps demonstrating some degree of active epistemic control. Playback experiments—where researchers cleverly position speakers in Kenya's Amboseli National Park to test reactions to a variety of recorded human voices—have shown that experienced matriarchs can even determine the threat level of human intruders by categorizing them according to ethnicity, gender, and age by using acoustic cues, olfactory cues, and dress—for adult Maasai tribesmen sometimes spear elephants in competition for grazing or in retaliation for attacks against humans, whereas Kamba tribesmen, or women/children of either tribe, usually pose no threat (Bates et al., ; Shannon et al., ). These matriarchs thus play a critical epistemic role in their herds; and the fitness of the herd is greatly diminished when matriarchs are killed by poachers, who target them for their large tusks.…”
Section: Putative Examples On Nonlinguistic Inferencementioning
confidence: 99%
“…The oldest member, the matriarch, retains knowledge about the landscape important for the group's survival (McComb et al 2001). In poached populations, where social structure is disrupted, groups have lower reproductive output and higher stress levels (Gobush et al 2008), with potentially long-term negative consequences for decisionmaking abilities (Shannon et al 2013).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…The oldest member, the matriarch, retains knowledge about the landscape important for the group's survival (McComb et al 2001). In poached populations, where social structure is disrupted, groups have lower reproductive output and higher stress levels (Gobush et al 2008), with potentially long-term negative consequences for decisionmaking abilities (Shannon et al 2013).Less is known about forest elephant social structure, as their dense and remote habitat makes it difficult to conduct behavioral studies. Observational studies at forest clearings or in savanna patches within forested regions suggest that sociality is different; groups are typically composed of an adult female and her calves (White et al 1993, Turkalo et al 2013.…”
mentioning
confidence: 99%